CHANGES IN AGRO-PHYSICAL PROPERTIES OF ORDINARY BLACK SOIL AT LONG-TERM LAND USE AND ECONOMIC INCENTIVES FOR ITS RECOVERY - Kramarov, S. M.; Bandura, L. P.; Artemenko, S. F.; Kramarov, O. S.; Pysarenko, P. V. (Scientific Progress & Innovations, 2021)
Ordinary black soils, unlike other subtypes of soils, are characterized by rather favorable agro-physical properties for cultivating crops. However, as a result of long-term agricultural use, the agro-physical properties of ordinary black soils begin to deteriorate. This is primarily connected with the fact that soil resources are considered as a source and means of making profit, without concern for the protection, preservation and reproduction of their agro-physical and agrochemical indicators. Thus, the primary natural value – the fertility of ordinary black soils is gradually being lost. At present, the rental use of land resources has led to negative consequences that are observed in land management: the spreading of erosion processes, low land productivity, catastrophic loss of humus from the soil and intensive physical degradation of indicators. Physical degradation results in over-compaction of the soil, loss of structure, deterioration of quality, formation of clods, crusts and cracks on the surface, and at the base of the arable layer – the plow pan. The main cause of physical degradation is excessive mechanical loading on the soil caused by heavy agricultural machinery, long-term use of traditional moldboard tillage, violation of crop rotations and excessive row crops’ growing, loss of humus, etc. All this is confirmed by the data of conducted comprehensive comparative assessment of agro-physical properties of ordinary black soils on arable land in comparison with characteristics of virgin land plots. The parameters of agro-physical soil properties were determined according to the existing standard methods. Agrarian science and practice have developed various measures for prevention and elimination of degradation, which makes the existing problem quite solvable at high culture of land use and new technical implements of soil tillage. Therefore, the National Action Plan to Combat Degradation and Desertification (p. 28) envisages the achievement of land degradation neutrality, recognized as one of the key objectives of Ukraine’s sustainable development for the period to 2030. However, the issues related to the search for economic incentives for measures to stop further development and spreading of degradation processes in the soil remain unsolved. New economic incentives for producers to improve the agro-physical properties of ordinary black soils have been proposed.